Mechanisms Associated with an Advance in the Timing of Seasonal Reproduction in an Urban Songbird - Fudickar, Adam M.; Greives, Timothy J.; Abolins-Abols, Mikus; Atwell, Jonathan W.; Meddle, Simone L.; Friis, Guillermo; Stricker, Craig A.; Ketterson, Ellen D. (Frontiers in Ecology and Evolution, 2017)
The colonization of urban environments by animals is often accompanied by earlier breeding and associated changes in seasonal schedules. Accelerated timing of seasonal reproduction in derived urban populations is a potential cause of evolutionary divergence from ancestral populations if differences in physiological processes that regulate reproductive timing become fixed over time. We compared reproductive development in free-living and captive male dark-eyed juncos deriving from a population that recently colonized a city (~35 years) and ceased migrating to that of conspecifics that live in sympatry with the urban population during winter and spring but migrate elsewhere to breed. We predicted that the earlier breeding sedentary urban birds would exhibit accelerated reproductive development along the hypothalamic-pituitary (HPG) axis as compared to migrants. We found that free-living sedentary urban and migrant juncos differed at the level of the pituitary when measured as baseline luteinizing hormone (LH) levels, but not in increased LH when challenged with Gonadotropin-Releasing Hormone (GnRH). Among captives held in a common garden, and at the level of the gonad, we found that sedentary urban birds produced more testosterone in response to GnRH than migrants living in the same common environment, suggesting greater gonadal sensitivity in the derived urban population. Greater gonadal sensitivity could arise from greater upstream activation by LH or FSH or from reduced suppression of gonadal development by the adrenal axis. We compared abundance of gonadal transcripts for LH receptor (LHR), follicle stimulating hormone receptor (FSHR), glucocorticoid receptor (GR), and mineralocorticoid receptor (MR) in the common-garden, predicting either more abundant transcripts for LHR and FSHR or fewer transcripts for GR and MR in the earlier breeding sedentary urban breeders, as compared to the migrants. We found no difference in the expression of these genes. Together the data suggest that advanced timing of reproduction in a recently derived urban population is facilitated by earlier increase in upstream baseline activity of the HPG and earlier release from gonadal suppression by yet-to-be-discovered mechanisms. Evolutionarily, our results suggest that potential for gene flow between seasonally sympatric populations may be limited due to urban-induced advances in the timing of reproduction and resulting allochrony